Influence of Anodization Temperature on Geometrical and Optical Properties of Porous Anodic Alumina(PAA)-Based Photonic Structures - Białek, Ewelina (Materials (Basel), 2020)
In this work, the influence of a wide range anodizing temperature (5–30 °C) on the growth and optical properties of PAA-based distributed Bragg reflector (DBR) was studied. It was demonstrated that above 10 °C both structural and photonic properties of the DBRs strongly deteriorates: the photonic stop bands (PSBs) decay, broaden, and split, which is accompanied by the red shift of the PSBs. However, at 30 °C, new bands in transmission spectra appear including one strong and symmetric peak in the mid-infrared (MIR) spectral region. The PSB in the MIR region is further improved by a small modification of the pulse sequence which smoothen and sharpen the interfaces between consecutive low and high refractive index layers. This is a first report on PAA-based DBR with a good quality PSB in MIR. Moreover, it was shown that in designing good quality DBRs a steady current recovery after subsequent application of high potential (U(H)) pulses is more important than large contrast between low and high potential pulses (U(H)-U(L) contrast). Smaller U(H)-U(L) contrast helps to better control the current evolution during pulse anodization. Furthermore, the lower PSB intensity owing to the smaller U(H)-U(L) contrast can be partially compensated by the higher anodizing temperature.